2020
DOI: 10.3390/rs12213590
|View full text |Cite
|
Sign up to set email alerts
|

Remote Sensing of Burn Severity Using Coupled Radiative Transfer Model: A Case Study on Chinese Qinyuan Pine Fires

Abstract: Burn severity mapping is critical to quantifying fire impact on key ecological processes and post-fire forest management. Satellite remote sensing has the advantages of high spatial-temporal resolution and large-scale monitoring and provides a more efficient way to evaluate forest fire burn severity than traditional field or aerial surveys. However, the proportion of tree canopy cover (TCC) affects the spectral signal received by remote sensing sensors from the background charcoal and ash. Consequently, not co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
(83 reference statements)
0
5
0
Order By: Relevance
“…The most promising method of monitoring forest territories today is remote aerospace monitoring. In most cases, hyperspectral sensors in the visible and near-infrared spectral ranges are used for monitoring forest areas [1][2][3][4][5][6] The initial information for mathematical modeling is the measurements data of vegetation elements spectral reflection coefficients in the broad spectral band from 400 to 2400 nm [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] .…”
Section: Problem Descriptionmentioning
confidence: 99%
“…The most promising method of monitoring forest territories today is remote aerospace monitoring. In most cases, hyperspectral sensors in the visible and near-infrared spectral ranges are used for monitoring forest areas [1][2][3][4][5][6] The initial information for mathematical modeling is the measurements data of vegetation elements spectral reflection coefficients in the broad spectral band from 400 to 2400 nm [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] .…”
Section: Problem Descriptionmentioning
confidence: 99%
“…They are a simple and effective empirical measurement method for different features and their characteristic information, and are widely used in remote sensing monitoring of soil parameters, crop growth, environmental changes, etc. [31][32][33][34]. In this study, 14 vegetation indices were selected as indicators for constructing the ET inversion model of the study area according to the requirements of the evapotranspiration inversion, as shown in Table 2.…”
Section: Vegetation Index Constructionmentioning
confidence: 99%
“…For high burn severity level, most of the overstory is scorched and the substratum can be charcoal or ash depending on the burn efficiency [11,51]. The CBI data (Figure 1) used in this study were obtained based on the algorithm proposed by Yin et al in 2020 [52], which was estimated by introducing tree canopy cover (TCC) into a coupled radiative transfer model. Through the field measured CBI and landscape photos, we verified the quantitative (R 2 = 0.92, RMSE = 0.2) and qualitative CBI estimation accuracy, which demonstrated good performance [52].…”
Section: Burn Severity Data and Random Sample Selectionmentioning
confidence: 99%
“…The CBI data (Figure 1) used in this study were obtained based on the algorithm proposed by Yin et al in 2020 [52], which was estimated by introducing tree canopy cover (TCC) into a coupled radiative transfer model. Through the field measured CBI and landscape photos, we verified the quantitative (R 2 = 0.92, RMSE = 0.2) and qualitative CBI estimation accuracy, which demonstrated good performance [52]. Location of the study area and the burn severity sample plots used in this study.…”
Section: Burn Severity Data and Random Sample Selectionmentioning
confidence: 99%
See 1 more Smart Citation